IDENTITAS SOSIAL BUDAYA DI DALAM KAIN TRADISIONAL ENDEK: TINJAUAN SOSIOLOGI FASHION DAN PAKAIAN (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
This study focuses on socio-cultural identity in endek traditional cloth. The purpose of this study is to describe and analyze the socio-cultural identity in endek traditional cloth. The method used in this study is a qualitative approach with a descriptive-explanative type. The theory used in analyzing this research is the sociology of fashion and clothing from Diana Crane & Laura Bovone. The results of this study reveal that the use of traditional endek cloth is currently increasing. The formation of the meaning of traditional endek cloth has certainly experienced a change, which was previously used only during religious ceremonies, but is currently used as a clothing material. This traditional endek cloth has very diverse motifs and colors, the motif that is widely used today is floral motifs with bright colors. Consumers will buy traditional endek cloth with the motifs and colors they like according to the use of the traditional endek cloth. The use of the endek traditional cloth describes as well as one of the expressions of the individual self. Marketing of endek traditional cloth is currently mostly done through social media. The appearance of endek traditional cloth on the international stage has made endek traditional cloth more widely known by outsiders. This endek traditional cloth can be a medium of communication in cultural interactions and become the cultural identity of our country. Keywords: Culture, Endek, Fashion, Social identity, Clothing